Development of Thematic Educational Game Eduklok Chemistry Based on Indonesian Local Wisdom - Cahya, Iis Nilam; Astuti, Ratih Dwi; Hanif, Septiana (Proceeding International Conference on Science and Engineering, 2020)
The purpose of this research is to develop a media in the form of educational games that contain local wisdom content, culture, culinary, and health, which are packaged in a snake and ladder game. In addition, this study also aims to test the quality and analyze user perceptions of the "Eduklok Chemistry" game product that has been developed. The method used in this research is to adapt the ADDIE model which includes the stages of analysis, design, and development. The quality of the developed product is tested by the expert judgment method using an expert assessment instrument to get a quality score. The study of users' perceptions of the product is carried out by the method of analyzing user responses to assess user perceptions in the form of response data. Quality test results by material experts that the product developed is included in the category of Very Good (SB) with a percentage of ideals of 100%. The results of quality tests by media experts on products developed are included in the category of Good (B) with a percentage of ideals of 76.92%. Meanwhile, the results of user perception studies show that most users respond Very Good (SB).